Self-Assessment of TEFL Teachers: Basis for the Development and Validation a Support Teaching Material - Galuhwardani, Cindyra (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study focused on developing and validating supplementary teaching materials for Teaching English as a Foreign Language (TEFL) to support Grade XII English teachers in Indonesia, particularly in Purwokerto. The study aimed to (1) evaluate teachers’ self-assessments related to teaching materials, students’ skills, and learning styles; (2) design supplementary teaching materials based on these assessments; (3) validate the materials; and (4) refine them following curricular validation feedback. The research utilized a descriptive method within a research and development framework. Questionnaires were the primary tools for assessing teacher and student needs and for validating the instructional materials. Data analysis employed statistical methods such as frequency counts, rankings, means, and weighted means. The findings indicated that teachers’ self-assessments provided essential insights for designing teaching materials tailored to the needs of both teachers and students. The developed materials were aligned with the Merdeka Curriculum and adopted a scientific, student-centred approach consistent with Indonesia’s educational framework. Topics were selected based on the Grade XII English syllabus. The proposed TEFL materials were deemed valid, with their strengths highlighted by teacher evaluators. The final output was refined based on evaluators’ recommendations to ensure quality and relevance.